Perioperative Complications in 155 Patients Who Underwent Oblique Lateral Interbody Fusion Surgery: Perspectives and Indications From a Retrospective, Multicenter Survey. Issue 1 (1st January 2017) - Abe, Koki; Orita, Sumihisa; Mannoji, Chikato; Motegi, Hiroyuki; Aramomi, Masaaki; Ishikawa, Tetsuhiro; Kotani, Toshiaki; Akazawa, Tsutomu; Morinaga, Tatsuo; Fujiyoshi, Takayuki; Hasue, Fumio; Yamagata, Masatsune; et al.
Abstract : Study Design: A retrospective multicenter survey. Objective: To investigate the perioperative complications of oblique lateral interbody fusion (OLIF) surgery. Summary of Background Data: OLIF has been widely performed to achieve minimally invasive, rigid lumbar lateral interbody fusion. The associated perioperative complications are not yet well described. Methods: The participants were patients who underwent OLIF surgery under the diagnosis of degenerative lumbar diseases between April 2013 and May 2015 at 11 affiliated medical institutions. The collected data were classified into intraoperative and early-stage postoperative (⩽1 mo) complications. The intraoperative complications were then subcategorized into organ damage (neural, vertebral, vascular, and others) and other complications, mainly related to instrumental failure. The collected data were also divided and analyzed based on whether the surgeon was certified to perform the surgery and the incidence of complications in the early (April 2013–March 2014) and late stages (April 2014–May 2015) of OLIF introduction. Results: In the 155 included patients, 75 complications were reported (incidence rate, 48.3%). The most common complication was endplate fracture/subsidence (18.7%), followed by transient psoas weakness and thigh numbness (13.5%) and segmental artery injury (2.6%). Almost all these complications were transient, except for three patients who had permanent damage: one had ureteral injury and two had neurological injury. Postoperative complications included surgical site infection (1.9%) and reoperation (1.9%). Whether the primary operator was experienced did not affect the incidence of complications. Regarding the introductory stage, the incidence of complications was 50% in the early stage and 38% in the late stage. Conclusion: The overall incidence of perioperative complications of OLIF surgery reached 48.3%, of which only 1.9% resulted in permanent damage. Our analysis based on surgeon experience indicated that the OLIF procedure could be performed without increasing incidence of complications, under the guidance of experienced supervisors. Level of Evidence: 3